Crown Ownership of Water in situ in Common Law Canada : Public Trusts, Classical Trusts and Fiduciary Duties - Matthews Glenn, Jane (Les Cahiers de droit, 2010)
A clear understanding of the private law rules relating to water in situ is a necessary pre-condition to the success of any public law management regime. This article thus examines the private law rules applicable in the common law provinces to determine if there are functional equivalents to Québec’s private law principle of res communis and its statutory notion of State “custodianship”.It concludes that while there is no direct functional equivalent to the concept of res communis, there is an acceptance — almost by default — of Crown ownership of water in situ, an acceptance reflected in the legislation of the western provinces. However, this Crown ownership is not full and absolute but rather limited, more in the nature of “custodianship” than “ownership”. This conclusion follows an exploration of three equitable institutions — the public trust, the classical trust and fiduciary duties. In each case, the argument for limitation is difficult, but not impossible, to make.